2014
DOI: 10.1016/j.stem.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin-CD44 Signaling in the Glioma Perivascular Niche Enhances Cancer Stem Cell Phenotypes and Promotes Aggressive Tumor Growth

Abstract: Summary Stem-like glioma cells reside within a perivascular niche and display hallmark radiation resistance. Understanding of the mechanisms underlying these properties will be vital for the development of effective therapies. Here we show that the stem cell marker CD44 promotes cancer stem cell phenotypes and radiation resistance. In a mouse model of glioma, Cd44−/− and Cd44+/− animals showed improved survival compared to controls. The CD44 ligand Osteopontin shared a perivascular expression pattern with CD44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
396
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(420 citation statements)
references
References 47 publications
19
396
1
4
Order By: Relevance
“…A previous study revealed that ERRα, combined with PGC1α, activates the promoter of osteopontin (OPN) gene and leads to elevated OPN expression in CRC cells (29). OPN is a glycoprotein secreted by a variety of tissues and enhances cancer stem cell phenotypes in various cancer types (30,31). Higher levels of OPN are produced by macrophages when co-cultured with cluster of differentiation 44-positive CRC stem cells, subsequently increasing the tumorigenicity of the CRC cells (32).…”
Section: Errα Expression (N=128) ------------------------------------mentioning
confidence: 99%
“…A previous study revealed that ERRα, combined with PGC1α, activates the promoter of osteopontin (OPN) gene and leads to elevated OPN expression in CRC cells (29). OPN is a glycoprotein secreted by a variety of tissues and enhances cancer stem cell phenotypes in various cancer types (30,31). Higher levels of OPN are produced by macrophages when co-cultured with cluster of differentiation 44-positive CRC stem cells, subsequently increasing the tumorigenicity of the CRC cells (32).…”
Section: Errα Expression (N=128) ------------------------------------mentioning
confidence: 99%
“…Over recent years CD44 along with other cell surface markers like CD133, CD90, CD24, ALDH, Nestin, EpCAM, and CD34 are also associated with CSC isolation and enrichment in various tumors [12]. In addition to its naturally occurring ligand, CD44 interacts with several ECM molecules including fibronectin galectin-8, laminin, fibrinogen, chondroitin sulfate [13], and osteopontin [14].…”
Section: Introductionmentioning
confidence: 99%
“…1E]. Binding of CD44 to stem cell niche-related extracellular matrix molecules, such as hyaluronan (HA) (9) and osteopontin (OPN), is in part predicated on the specific transcript variants expressed (10), and OPN-CD44 signaling promotes aggressive tumor growth (11). Although CD44 expression has been shown to promote both chronic and acute myeloid leukemia stem cell (LSC) maintenance in mouse models (12)(13)(14), CD44 splice isoform switching and cognate ligand expression as well as malignant reprogramming of human progenitors into self-renewing LSCs had not been elucidated.…”
mentioning
confidence: 99%